اثر موعد الزارعة و الكثافة النباتية على بعض الصفات المورفولوجية لصنف الترمس الابيض البلدي (المر) Lupinus albus تحت ظروف الساحل السوري - محمد, يوسف; خلاصي, حسام الدين; ديوب, علي (Latakia University Journal -Biological Sciences Series, 2018)
نفذ البحث في الموسم الزراعي 2016-2017 في قرية دوير رسلان التابعة لمحافظة طرطوس بثلاث موعد زراعة (20 تشرين الثاني – 10 كانون الاول – 1 كانون الثاني) مع ثلاث كثافات (12 – 14 – 16 نبات/م²) وصممت التجربة بطريقة القطاعات العشوائية المنشقة حيث شغلت موعد الزراعة القطع الرئيسية وشغلت الكثافة النباتية القطع المنشقة لمرة واحدة لدراسة تأثير موعد الزراعة و الكثافة النباتية على بعض الصفات المورفولوجية لنبات الترمس الابيض. أظهرت النتائج تفوق نباتات الموعد المبكر (20 تشرين الثاني) في صفة ارتفاع النبات بمتوسط 64 سم و في صفة مساحة المسطح الورقي بمتوسط 24.367 الف. م2 /هـــ و في صفة طول القرن بمتوسط 7.50 سم. اما بالنسبة للكثافة النباتية فقد تفوقت نباتات الكثافة 2 نبات/م² في صفة ارتفاع النبات بمتوسط 65.6 سم و في صفة طول القرن بمتوسط 8.13 سم بينما تفوقت نباتات الكثافة 16 نبات/م² في صفة مساحة المسطح الورقي بمتوسط 24.213 الف. م2 /هـــ . The research was carried out in the agricultural season 2016-2017 the village of DweirRaslan Tartous governorate with three planting dates (20 November - 10 December - 1 January) and three densities (12 - 14 - 16 plants / m2) Where the planting time was the main pieces and the plant density occupied the dissecting pieces once to study the effect of planting date and plant density on some morphological characteristics of white thermos plant. The results showed that dates of the early dates (November 20) were higher in plant height, with an average of 64 cm and surface area of ​​the paper surface at an average of 24.367 thousand. M 2 / ha and in shape of the length of the century with an average of 7.50 cm. As for the plant density, the plants of density12 plants / m 2 in the height of plant exceeded an average of 65.6 cm and length of the century with an average of 8.13 cm, while the plants of density 16 plants / m 2 in the area of ​​paper area average 24.213 thousand. M2 / ha